Regenerative Therapy for Chronic Heart Failure: Prospects for the Use of Cellular and Acellular Technologies - I. S. Dolgopolov; M. Yu. Rykov; V. V. Osadchij (Архивъ внутренней медицины)
Cardiovascular diseases are the second leading cause of death and disability worldwide after malignancies. Heart failure (HF) has a large impact not only on the economics of healthcare but also on the quality of life, functionality and life expectancy of patients. Pharmacological and non-pharmacological therapies have been developed, but these medical therapies have limited effects to cure patients with severe CH. Heart transplantation is limited due to the low number of donor organs. Human cardiac potential for spontaneous repair is insignificant, so regenerative therapy is in great demand as a new treatment strategy. Currently, there are several strategies for heart regeneration. Transplantation of somatic stem cells was safe and modestly improved cardiac function after myocardial infarction and in patients with CF mainly through paracrine mechanisms. Alternatively, new cardiomyocytes could be generated from induced pluripotent stem cells (iPSCs) to transplant into injured hearts. However, several issues remain to be resolved prior to using iPSC-derived cardiomyocytes, such as a potential risk of tumorigenesis and poor survival of transplanted cells in the injured heart. Recently, direct cardiac cell-free reprogramming has emerged as a novel technology to regenerate damaged myocardium by directly converting endogenous cardiac fibroblasts into induced cardiomyocyte-like cells to restore cardiac function. Many researchers have reported direct reprogramming of the heart in vivo in animal and human cells. In this review, we review the current status of cardiac cell-based and cell-free regenerative technology, a great hope to treat cardiovascular diseases in clinical practice.